Factors influencing students academic performance: Case of Mai Idris Alooma Polytechnic Geidam - Adamu, Ibrahim Ghide; Olayinka, Aminu Abdulrahim; Usman, Mohammed (Journal of Social, Humanity, and Education, 2024)
Purpose: This study aimed to investigate the factors that influence the performance of students in Mai Idris Alooma Polytechnic Geidam Yobe State in the Northeastern Nigeria. Research methodology: The paradigm of this study is to use the final-year students of Mai Idris Alooma Polytechnic Geidam as independent variables. The dependent variables included factors influencing students’ academic performance. Factors included a) personal conditions, b) study habits, c) home-related aspects, d) school-related aspects, and e) lecturer-related factors. Results: The study identified different factors and the highest impact among the variables that influence the academic performance of students in institutions other than those traditionally studied. Among these five (5) domains, lecturer-related aspects and personal condition factors fall behind school-related factors. Nonetheless, both categories were still deemed highly impactful. Conversely, home-related factors and study habits had little effect on students’ academic performance in the case study. Limitations: The research analysis was limited to a self-report questionnaire gathered from final-year students Mai Idriss Alooma Polytechnic Geidam in October 2023. Contribution: With the outcome of this research, all students, particularly year one prospective students, and those students who are not as academically strong will be informed about the factors that influence their academic performance.